Beyond the Great Divergence: Household Income in the Indian Subcontinent, 1500–1870 - Carvalhal, Hélder; Lucassen, Jan (International review of social history, 2025)
The article explores the evolution of household income in India before the late nineteenth century. At a time when criticism of estimates of global real wages challenges the assumptions arising from the Great Divergence Debate, we aim to provide alternative ways of contributing to the discussion. By looking at individual and household income, as well as consumption levels in different parts of India, we found that members of the household other than the head (namely women) supplied a larger part of its total income than an analysis of wage differentials would suggest. Moreover, we argue that India, in the centuries under review, had a functioning labour market, despite several impediments. This adds to the value of our data as building blocks to reconstruct real wages and, consequently, to better understand welfare levels. Nevertheless, the decline in the Indian skill premium suggests that channels of social mobility decreased over time. The implications of all these findings for the Great Divergence Debate depend on the extent to which our approach also has consequences for our view on household income in other parts of Eurasia. Certainly, they call for a nuanced approach to Indian economic development during the period.